1995
DOI: 10.1080/07399339509516210
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of experiences of sexual violence for women with abusive partners

Abstract: We assessed the incidence of sexual violence, physical violence, physical health symptoms, gynecological symptoms, and risk behaviors for contracting an STD or HIV infection in women who had used a shelter for women with abusive partners. In addition, we investigated the relationships between sexual violence and the frequency of physical health symptoms, including specific gynecological symptoms. Results indicated that one fourth of the women interviewed had experienced sexual violence and nearly two thirds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 15 publications
2
108
0
9
Order By: Relevance
“…10 Studies on women with histories of abuse have shown that this population of women also tend to have higher prevalences of physical health problems, including neurological problems, gastrointestinal problems, and gynecological problems. 11,12 The particular health care service needs of abused women are an important factor in considering the health care needs of incarcerated women.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies on women with histories of abuse have shown that this population of women also tend to have higher prevalences of physical health problems, including neurological problems, gastrointestinal problems, and gynecological problems. 11,12 The particular health care service needs of abused women are an important factor in considering the health care needs of incarcerated women.…”
Section: Discussionmentioning
confidence: 99%
“…Among women who disclosed victimization to employers, informal and formal job supports were offered. Workplace supports led to short-term job retention, but fear and safety issues mitigated employers' attempts to retain workers.The effects of intimate partner violence on women's physical and mental health and on the public health infrastructure within the United States have received a fair amount of attention in recent history (Dutton, Haywood, & El-Bayoumi, 1997;Eby, Campbell, Sullivan, & Davidson, 1995;Logan, Walker, Cole, Ratliff, & Leukefeld, 2003;. Despite this research, minimal attention has focused on the effects of intimate partner violence on women's labor force (Lloyd, 1997;Lloyd & Taluc, 1999;Raphael & Tolman, 1997;Riger, Ahrens, & Blickenstaff, 2000;Tolman & Raphael, 2000).…”
mentioning
confidence: 99%
“…1 Men who commit physical abuse often commit sexual abuse. 11 Between 41 12 and 68 % 6 of women who are physically abused by an intimate partner are also sexually abused by them. In studies of physically abused women recruited from the community, 44-48 % reported their abuser also sexually assaulted and/or coerced them into unwanted sexual activity, 7,13,14 including 15 % who reported that their partner physically forced them to have sex and 13 % who reported that their partner made them have sex without a condom.…”
mentioning
confidence: 99%